นักการเมืองถิ่นสครี : กรณีศึกษาองค์กรปกครองส่วนท้องถิ่นในจังหวัดลำปาง - กุลธิดา สิงห์สี (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
The aim of this research was to study 1) the backgrounds and factors supporting the entering to power of local woman politicians 2) the forms of exercising and maintaining of power and 3) the comparison of the forms of entering, practicing and maintaining of power. The study was a qualitative research employing the methodology of document analysis, observations and in-depth interviews as the major instruments for collecting data. This analysis description Research aimed to describe the process of causes by studying the relevant documents and interviewing the residents. The findings showed that 1) backgrounds and factors supporting the entering to power of the local woman politicians were dissimilar 2) the form of exercising power found that woman leaders mainly had the power to decision-making and usually provided opportunities for all parties to be involved in the work 3) the preservation of political power of local woman politicians was by supporting group members to be elected, building relationships with local politicians, subordinates and organizations both inside and outside the organizations, responding to the people’s needs and building image and 4) the results of comparison found the local woman politicians had similar form for using and maintaining power but different form for entering to the power.